2023
DOI: 10.3389/fsurg.2022.907234
|View full text |Cite
|
Sign up to set email alerts
|

A male congenital pelvic arteriovenous malformation diagnosed by abdominal ultrasound: A case report and literature review

Abstract: Congenital pelvic arteriovenous malformation (AVM) is a rare vascular abnormality whereby arteries and veins are directly connected with malformed vascular plexus. Owing to its low incidence and nonspecific symptoms, the ultrasonographic characteristics of congenital pelvic AVM in males have been infrequently studied. A 30-year-old man visited our hospital complaining of progressive pain in the right lower abdomen and lumbar area since 2 months previously. Abdominal ultrasound (US) was performed at the initial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…Additionally, surgical excision is often invasive, requiring sacrificing part of the adjacent pelvic organs, and bleeding as well. 1 , 4 , 13 Therefore, embolization is normally the treatment of choice, with various embolic agents such as coils, embolic particles, liquids.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, surgical excision is often invasive, requiring sacrificing part of the adjacent pelvic organs, and bleeding as well. 1 , 4 , 13 Therefore, embolization is normally the treatment of choice, with various embolic agents such as coils, embolic particles, liquids.…”
Section: Discussionmentioning
confidence: 99%
“… 1 , 5 Reviewing in literature, there are approximately 20 cases of pAVM reported. 1 , 2 , 3 , 4 , 6 , 7 , 8 , 9 , 10 In male patients, pAVM presents with various symptoms such as pelvic discomfort, hematospermia, erectile dysfunction, hematuria, leading to difficulties in diagnosis. 2 , 11 In this report, we present a case of pAVM mimicking a BPH, which is a common issue of male at this age.…”
Section: Case Presentationmentioning
confidence: 99%
See 1 more Smart Citation
“…There are multiple treatment options for pelvic AVM, including ligation of the afferent artery, excision, and embolization. Nevertheless, it has been shown that the surgical method is typically ineffective and fraught with complications such as hemorrhage injury to adjacent organs, and a possibility of recurrence [ 18 ]. The first transcatheter embolization was carried out in the early 1970s [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…During early 1980s, embolization was established as the treatment of choice for pelvic AVMs [ 20 ]. Due to the lower morbidity, mortality, and invasiveness, embolization is the treatment of choice for pelvic AVM [ 18 ]. A study by Cansaran et al in 2021 reported a case of AVM around the bladder that was first mistaken for an appendicular abscess and was excised by open surgery.…”
Section: Discussionmentioning
confidence: 99%